El sexo del conductor de la empresa que prevalece en las empresas registradas como personas naturales en el Perú periodo 2020-2024 - Marichín Huansi, John Geyner (2025)
In sexist societies like Peru, it is generally assumed that men are the majority leaders in business management, with the assumption that women are less qualified to do so. However, this research demonstrates the opposite. This doctoral research analyzes the stock of companies operating in Peru during the 2020–2024 five-year period, focusing on the gender of the company's director. To this end, the historical development of the country's business stock is studied, which determines this thesis' quantitative nature. It is also descriptive because it recounts the behavior of the variables. It has a non experimental design. It concludes by demonstrating that companies incorporated as individuals and led by women predominate in the business stock (51.11%). The companies that entered the market during the five-year period under investigation, registered as individuals, were run by women (52.92%), and the predominant activity was beauty salons (71.64%). A review of the companies closed during the same period, considered as individuals, showed that they were managed by men (50.88%) and were linked to the construction sector (81.46%). The department of the country with the most registered companies was Lima (36.66%), which were run by women.